Dietary Pattern and Nutritional Status among Chronic Kidney Disease Patients (Journal of Preventive and Social Medicine, 2026)
Background: Chronic kidney disease is recognized as a serious health problem in both developed and developing countries. In recent years, an increasing incidence of chronic kidney disease has been observed worldwide, and the number of patients need special attention.Objectives: To assess the dietary pattern and nutritional status of the patient with chronic kidney disease.Methods: A cross-sectional study was carried out among 253 respondents of National Institute of Kidney Disease and Urology (NIKDU) and Anwer Khan Modern Medical College Hospital, Dhaka. Data were collected by convenient sampling through face-to-face interview using a semi-structured questionnaire. For nutritional assessment, “Asian criteria” BMI cut-off was performed. Dietary pattern was assessed with food frequency questionnaire, number of major meals per day, light meal, skipped meal for last 7 days. Data were analysed by SPSS 25 software.Results: The study found that highest number (23.7%) of the respondents were in age group 46 to 55 years and about 51% of the respondents were male. Assessment of nutritional status (BMI) of the respondents who were not oedematous (n=83) showed that 68.7% of the respondents were pre obese, 9.6% were obese and 14.5% were overweight. Among the respondents 85.4% took three meals a day and 53.3% took 1.5 litres of water daily, 68.8% of them did not take extra salt during meals, 36% of them strained vegetables in boiling water prior cooking. Older CKD patients (>45 years) showed higher proportion of obesity (p